1996
DOI: 10.1097/00007632-199601150-00014
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evidence of Absorption of Sequestration-Type Herniated Disc

Abstract: These findings suggest that organization is not a main course for this type of herniated disc and that a kind of "absorption" process occurs predominantly in the healing stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(59 citation statements)
references
References 11 publications
5
49
0
5
Order By: Relevance
“…Slavin et al hypothesized [23] that cartilaginous tissue resorption results from enzymatic degradation and phagocytosis as a result of inflammation and neovascularization due to an autoimmune response [24,25]. Some studies have revealed neovascularization at the periphery of the sequestrated disc and the presence of macrophages and T cells in the vascularized areas [26][27][28]. In our study, all patients with reduced pseudotumors demonstrated contrast enhancement of their pseudotumor on MRI after Gd administration.…”
Section: Discussionsupporting
confidence: 57%
“…Slavin et al hypothesized [23] that cartilaginous tissue resorption results from enzymatic degradation and phagocytosis as a result of inflammation and neovascularization due to an autoimmune response [24,25]. Some studies have revealed neovascularization at the periphery of the sequestrated disc and the presence of macrophages and T cells in the vascularized areas [26][27][28]. In our study, all patients with reduced pseudotumors demonstrated contrast enhancement of their pseudotumor on MRI after Gd administration.…”
Section: Discussionsupporting
confidence: 57%
“…These, however, are known to be infiltrated with macrophages and T-cells, which may contribute to the levels of production of mediators. 13,[19][20][21][22] The disc material in sequestrated herniations is also in a different anatomical location to the contained or semicontained specimens in the group with low back pain only. The reasons for increased production of inflammatory mediators by the nucleus pulposus in patients with discogenic low back pain are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…When an intervertebral disc is herniated, nuclear material extrudes into the spinal canal. Within a short time, neocapillarisation begins in and around the extruded nucleus material [15][16][17][18][19] and inflammation occurs with an increased presence of macrophages [17][18][19]. As the avascular anaerobic disc provides an ideal environment for anaerobic bacteria, it is plausible that these low virulent anaerobic bacteria may enter the disc and give rise to a slowly developing infection.…”
Section: Introductionmentioning
confidence: 99%